Alasan Pentingnya Bainduak Bagi Perantau Minangkabau di Masyarakat Hukum Adat Lubuk Sikaping Pasaman - Vensuri, Hamzah; Sulastriyono, Sulastriyono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The purposes of this study are to identify and analyze the importance of bainduak by female immigrants who come to Lubuk Sikaping area of ​​Pasaman Regency and analyze the legal effect`s position of female immigrants who bainduak in the law of adat`s marriage in Lubuk Sikaping Pasaman Regency. The method of this study uses the juridical empiric which observes about the reactions and interactions that occur when the system norms implements in society. The data are analysed by using qualitative and data are presented in descriptive approach by using inductive in conclusion. The results of this study show that: The reasons of female immigrants of Minangkabau doing bainduak in Lubuk Sikaping Pasaman Regency are: (a)